Whole Cell Actinobacteria as Biocatalysts - Anteneh, Yitayal Shiferaw; Franco, Christopher Milton Mathew (Frontiers in Microbiology, 2019)
Actinobacteria are essential to the pharmaceutical industry because they produce a range of bioactive compounds that are essential for human health. Their ability to synthesize a variety of chemical structures is due to their biochemical versatility in that they contain a plethora of enzymes that catalyse both degradative and synthetic reactions. While many processes utilise single or multiple purified enzymes, there is a role for whole organisms in catalysing a series of reactions to achieve a processing goal. This chapter examines the role of whole actinobacteria in biocatalysis.